1984
DOI: 10.1017/s1742758400004938
|View full text |Cite
|
Sign up to set email alerts
|

Inherited sterility among Agrotis ipsilon laboratory population, exposed to gamma irradiation

Abstract: Full-grown pupae Agrotis ipsilon were irradiated with 5 or 10 krad and crossed with unirradiated female. The F, progeny were more sterile than parents. Percentage of mated female of F, was greatly reduced while the mating frequency was increased. Less inseminated females were among the F,, particularly when the female inherited the sterility. The mortality among larvae of the F, was high and dose-dependent, and that among F 2 larvae was even higher. The sex ratio of the F, progeny was altered in favour of male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…Where, gamma radiation lethal doses of LD 25 and LD 50 increased larval and pupal mortality, larval and pupal durations, as well as reduce on the percentage of adults emerging and growth index. These results are in agreement with Saleh, Gaaboub, Rawash, and El-Sawaf (1981) who recorded a decline in pupation and adult emergence percent in UV-irradiated Culex pipens and Aedes aegypti, El-Naggar, Megahed, Sallam, and Ibrahim (1984) who found, the mortality among Agrotis ipsilon larvae of the first generation was high and increased as the dose of gamma radiation increased, Pransopon, Sutantawong, Hormchan, and Wongpiyasatid (2000) who reported that, the survival of Helicoverpa armigera immature stages decreased with the increasing of gamma radiation dose level, Sallam, El-Shall, and Mohamed (2000) who recorded that, the spiny bollworm Earias insulana larvae reaching the adult stage decreased in number as the irradiation dose increased and Gabarty (2011) who recorded that gamma irradiation LD 50 and LD 95 doses affected the biological parameters of the greasy cut-worm A. ipsilon. Similar observations were recorded by Hassan, Amer, Hammad, Gabarty, and Selim (2017) who found that, gamma irradiation affected the biological activity of C. pipiens during the first and second generations, also the larval, pupal mortality and duration were increased, as well as the percentage of adults emergence and growth index were decreased as the doses increased.…”
Section: Latent Effect Of Gamma Irradiation On Some Biological Aspectsupporting
confidence: 92%
“…Where, gamma radiation lethal doses of LD 25 and LD 50 increased larval and pupal mortality, larval and pupal durations, as well as reduce on the percentage of adults emerging and growth index. These results are in agreement with Saleh, Gaaboub, Rawash, and El-Sawaf (1981) who recorded a decline in pupation and adult emergence percent in UV-irradiated Culex pipens and Aedes aegypti, El-Naggar, Megahed, Sallam, and Ibrahim (1984) who found, the mortality among Agrotis ipsilon larvae of the first generation was high and increased as the dose of gamma radiation increased, Pransopon, Sutantawong, Hormchan, and Wongpiyasatid (2000) who reported that, the survival of Helicoverpa armigera immature stages decreased with the increasing of gamma radiation dose level, Sallam, El-Shall, and Mohamed (2000) who recorded that, the spiny bollworm Earias insulana larvae reaching the adult stage decreased in number as the irradiation dose increased and Gabarty (2011) who recorded that gamma irradiation LD 50 and LD 95 doses affected the biological parameters of the greasy cut-worm A. ipsilon. Similar observations were recorded by Hassan, Amer, Hammad, Gabarty, and Selim (2017) who found that, gamma irradiation affected the biological activity of C. pipiens during the first and second generations, also the larval, pupal mortality and duration were increased, as well as the percentage of adults emergence and growth index were decreased as the doses increased.…”
Section: Latent Effect Of Gamma Irradiation On Some Biological Aspectsupporting
confidence: 92%
“…Pupal weight was significantly decreased at 125 Gy onwards from 1.51g/10 pupae (125 Gy) to 0.89 g/10 pupae (200 Gy). The similar results were reported by El-Naggar, Megahed, Sallam, & Ibrahim (1984) reported that the pupal weight was significantly decreased at radiation doses higher than 100 Gy in F 1 generation and radiation doses higher than 50 Gy in F 2 generation of Agrotis ipsilon.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…This technique as a successful control device for suppressing and combating many lepidopteraus insect pests, including A. ipsilon has been studied (Abdel Hamid, 2004;EL-Kady, Salem, & Hekal, 1983;ElNaggar, Ibrahim, El-Shall, 1999;El-Naggar, Megahed, Sallam, & Ibrahim, 1984, 1985Ibrahim, 1981).…”
Section: Introductionmentioning
confidence: 99%